2020
DOI: 10.1021/acsomega.0c04847
|View full text |Cite
|
Sign up to set email alerts
|

A Screening of Neuraminidase Inhibition Activities of Isoquinolone Alkaloids in Coptis chinensis Using Molecular Docking and Pharmacophore Analysis

Abstract: Coptis chinensis has been long used as the potential herbal remedy for the treatment of influenza A infection. The six isoquinolone alkaloids extracted from C. chinensis rhizomes are reported to have good inhibition activity on neuraminidase (NA) of Clostridium perfringens, A/H1N1/1918, and recombinant NA-1; however, the study of the effect of these candidates on other NAs of threatening influenza A causing pandemic and seasonal flu recently has not considered yet. The purpose of this study is to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The types and contents of alkaloids of CR in different growth environments and growth stages vary greatly. Previous studies only focused on chemical compounds (Li et al, 2012;Meng et al, 2018;Hao et al, 2020), pharmacological activities (Hong et al, 2012;Kim et al, 2016;Akiyama et al, 2019;Ma et al, 2019;Teklemichael et al, 2020), molecular biology (Kitamura et al, 2018;Le et al, 2020;Chen et al, 2021), and product specifications [30] of CR, with few reporting the internal relationship between appearance characteristics and quality of medicinal materials.…”
Section: Discussionmentioning
confidence: 99%
“…The types and contents of alkaloids of CR in different growth environments and growth stages vary greatly. Previous studies only focused on chemical compounds (Li et al, 2012;Meng et al, 2018;Hao et al, 2020), pharmacological activities (Hong et al, 2012;Kim et al, 2016;Akiyama et al, 2019;Ma et al, 2019;Teklemichael et al, 2020), molecular biology (Kitamura et al, 2018;Le et al, 2020;Chen et al, 2021), and product specifications [30] of CR, with few reporting the internal relationship between appearance characteristics and quality of medicinal materials.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between peptides and proteins were analyzed using a protein–ligand interaction profiler (PLIP). 12 Finally, molecular visualization of the amino acid residue interaction at the active protein site was achieved using PyMol.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that berberine could directly have antiviral activities on the infection of the influenza virus in vitro and in vivo (22). Berberine, as a main bioactive compound of Coptis chinensis rhizome, had a higher affinity to six selected proteins than commercial drugs such as oseltamivir, zanamivir, and natural binding ligand sialic acid to inhibit NA (48).…”
Section: Antiviral Effects Of Berberine On Influenza Virusesmentioning
confidence: 98%